2002
DOI: 10.1164/rccm.200201-027oc
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Gram-Negative Translocation Reduces the Severity of Hepatopulmonary Syndrome

Abstract: Hepatopulmonary syndrome (HPS) is characterized by intrapulmonary vascular dilatations and an increased alveoloarterial oxygen difference (AaPO(2)). These abnormalities are related to augmented pulmonary nitric oxide (NO) production, dependent primarily on increases in the expression and activity of inducible NO-synthase (iNOS) within pulmonary intravascular macrophages and, to a lesser extent, of endothelial NOS (eNOS). Production of iNOS by pulmonary intravascular macrophages might be related to translocated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

13
112
1
11

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(137 citation statements)
references
References 23 publications
13
112
1
11
Order By: Relevance
“…When we evaluated lipid peroxidation in the two models of cirrhosis, animals in the EX group had significantly higher values compared to those in the CO group, and the level of TBARS and QL were elevated in the lung and liver in both groups. This overproduction of ROS might occur in several pathophysiological situations and may explain the finding that in our study, the levels of TBARS and QL were high (22,23) . Physiological defense mechanisms are effective in preventing or counteracting the damage caused by free radicals, which can include a set of endogenous antioxidant enzymes such as superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx).…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…When we evaluated lipid peroxidation in the two models of cirrhosis, animals in the EX group had significantly higher values compared to those in the CO group, and the level of TBARS and QL were elevated in the lung and liver in both groups. This overproduction of ROS might occur in several pathophysiological situations and may explain the finding that in our study, the levels of TBARS and QL were high (22,23) . Physiological defense mechanisms are effective in preventing or counteracting the damage caused by free radicals, which can include a set of endogenous antioxidant enzymes such as superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx).…”
Section: Discussionsupporting
confidence: 53%
“…PPH patients exhibit arterial hypoxemia and arterial oxygenation that is significantly worse when comparing liver transplantation candidates with normal vascular resistance as determined by echocardiography Doppler (16) . In the BDL model, hypoxemia may be associated with bacterial translocation occurring in 45%-75% of cirrhotic animals whereby the induced hepatocellular damage prevents adequate blood filtration and promotes the development of portosystemic shunts; this phenomenon dramatically decreases the phagocytic ability of the liver, and it also allows the entry of bacteria and endotoxins into the lung circulation (23) . Furthermore, studies have reported arterial hypoxemia in BDL animals, which contributes to a reduction in the values of PaO 2 due to increased volume of lung shunt (32) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During phagocytosis, the activation of numerous macrophages results in the secretion of products such as cytokines and nitric oxide into the extracellular medium, nitric oxide being a potent vasodilator and also being involved in mechanisms of imbalance between the antioxidant and oxidative systems. (24) Nitric oxide functions as a molecular signaler (mediating vasodilatation when produced at low concentrations by nitric oxide synthase in endothelial vascular cells) and as a highly toxic oxidant source (when produced at high concentration by nitric oxide synthase in macrophages in the inflammatory process), thereby promoting intrapulmonary vasodilatation followed by hypoxemia. (25) Many authors have reported that, in the presence of cirrhosis, there is a considerable increase of lipoperoxidation due to the formation of reac-…”
Section: Discussionmentioning
confidence: 99%
“…9 During the progression of HPS, increased tumor necrosis factor alpha production associated with bacterial translocation contributes to intravascular macrophage accumulation and inducible nitric oxide synthase expression. 10 Recently, increased intravascular macrophage heme oxygenase-1 expression and carbon monoxide overproduction have been identified after common bile duct ligation and also appear to contribute to changes in the microvasculature. 11 In human HPS, pulmonary NO overproduction, as assessed by exhaled NO levels has also been found.…”
mentioning
confidence: 99%